2018
DOI: 10.1088/1361-6382/aac6a4
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic analysis of the EPRL model with timelike tetrahedra

Abstract: We perform the stationary phase analysis of the vertex amplitude for the EPRL spin foam model extended to include timelike tetrahedra. We analyse both, tetrahedra of signature − − − (standard EPRL), as well as of signature + − − (Hnybida-Conrady extension), in a unified fashion. However, we assume all faces to be of signature −−. The stationary points of the extended model are described again by 4-simplices and the phase of the amplitude is equal to the Regge action. Interestingly, in addition to the Lorentzia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(68 citation statements)
references
References 113 publications
(389 reference statements)
6
62
0
Order By: Relevance
“…But the discussion and results are valid or any other spinfoam models which have both the correct large spin asymptotics, and the flatness (e.g. the model with timelike tetrahedra [43] and its recent asymptotical analysis [10]). …”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…But the discussion and results are valid or any other spinfoam models which have both the correct large spin asymptotics, and the flatness (e.g. the model with timelike tetrahedra [43] and its recent asymptotical analysis [10]). …”
Section: Introductionmentioning
confidence: 82%
“…[6][7][8][9][10]). It has been shown that if one doesn't consider the spin-sum, but consider the spinfoam (partial) amplitude with fixed spins, the large spin asymptotics of the amplitude give the Regge action of gravity, being a discretization of the Einstein-Hilbert action on the triangulation.…”
Section: Introductionmentioning
confidence: 99%
“…For the given normal N 0 i (see [8]) with the norm c i = |N 0 i | 2 ∈ {−1, 1} we can decompose the bivector B as follows…”
Section: Bivector Decompositionmentioning
confidence: 99%
“…The bivectors at this stationary point are denoted B 0 ij (in the simplex frame) and B 0 ′ ij = (g 0 i ) −1 B 0 ij (see the beginning of section 3). The geometric bivectors B ∆ ij are described in [8] and appear in section 6.…”
Section: A Notationmentioning
confidence: 99%
See 1 more Smart Citation